Social Control Mechanisms of the Community toward Alcoholic Beverage Vendors in Air Dingin Village, Pesisir Selatan Regency - Rizza Armelvia Sari (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The phenomenon of the circulation of illegal alcoholic beverages in certain areas has generated negative impacts on the community, particularly on the younger generation. This issue requires serious attention given the weak existing monitoring mechanisms, thus necessitating an in-depth examination of the social control efforts carried out by the local community. This study aims to describe the various forms of social monitoring implemented by the community and to identify the obstacles encountered in efforts to control the circulation of illegal alcoholic beverages in Kampung Air Dingin, Basa Ampek Balai Tapan District. The research employed a qualitative design with a descriptive approach. Data collection techniques were carried out through field observation and in-depth interviews with key informants. Data analysis refers to F. Ivan Nye’s theory of social control. The findings indicate that community monitoring is divided into two categories. First, direct control includes patrol operations and raids by police officers, counseling activities, the confiscation of evidence, monitoring by local youth groups, and warnings from community leaders. Second, indirect control is implemented through religious guidance by religious leaders and the magrib mengajar program initiated by the youth. The effectiveness of monitoring remains constrained by several factors, namely suboptimal law enforcement, the still-low level of residents’ awareness, and the ongoing tradition of consuming alcoholic beverages during wedding ceremonies. Stronger synergy between the community and law enforcement officers is needed to achieve effective social control.